KINERJA PEGAWAI DAAM PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA TOMBATU DUA KECAMATAN TOMBATU UTARA KABUPATEN MINAHASA TENGGARA - Baginda, Anita Sartika Toiw; Mandey, Jantje; Kolondam, Helly (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract : This study in order to obtain a Bachelor's degree thesis Tier One at the Faculty of Social and Political Sciences, University of Sam Ratulangi Manado. Moving on from the pre-study conducted by researchers, that turns Implementation of Land and Building Tax Collection in the Village Tombatu Two found no universal agreement or cooperation between tax collectors officer with the taxpayers. Thus, the researchers see the need to be studied and considered the implementation of tax collection in the village Tombatu Two. This research uses qualitative research methods. Data were collected starting from the stage of observation, interviews and literature.The conclusion that can be drawn from this research is that it is found not optimal performance of employees in the implementation of land and building tax collection in the village Tombatu Two. Because in practice there has been no cooperation between tax officials and taxpayers. The village government should seek more optimal in the implementation of land and building tax collection so that the problems that exist in the village can be resolved and useful to the progress of the village into a better direction.Keywords: Performance Officer, Land and Building Tax Collection